Preoperative antibiotic prophylaxis in mastectomy: A retrospective comparative analysis of 1413 patients with breast cancer. (September 2022) - Tamminen, Anselm; Koskivuo, Ilkka
Background and objective: The reported rate of surgical site infections (SSIs) in breast cancer surgery varies widely in previous literature. The use of antibiotic prophylaxis is controversial but recommended by several guidelines. The aim of this study was to evaluate the efficacy of routine antibiotic prophylaxis in patients with breast cancer undergoing mastectomy. Methods: In this retrospective single-institution study, we reviewed 1413 consecutive female breast cancer patients who underwent mastectomy and/or axillary lymph node surgery between years 2012 and 2019. Prophylactic antibiotics for all patients undergoing mastectomy was introduced in our hospital in 2016 and before that the prophylaxis was prescribed individually on surgeons' preference. All patient records for 30 postoperative days were evaluated in detail and all SSIs were recorded. The rate of SSIs was compared between patients who received antibiotic prophylaxis and those who did not. A multivariate logistic regression model was used to define the odds ratio (OR) for the efficacy of antibiotic prophylaxis. Results: A total of 335 patients underwent mastectomy without antibiotic prophylaxis and 1078 with prophylaxis. The rate of SSIs was 6.9% in patients who received prophylaxis and 6.3% in patients without prophylaxis ( p = 0.70). The rate of SSIs was similar before and after the introduction of regular antibiotic prophylaxis and there was no difference in any of the patient subgroups investigated. In multivariable logistic regression analysis, the OR for antibiotic prophylaxis was 1.04 (95% CI: 0.62–1.73, p = 0.88). Conclusions: Routine use of antibiotic prophylaxis did not reduce the rate of SSIs in mastectomy. Unselective antibiotic prophylaxis for all patients does not seem mandatory in mastectomy.